Assessing high performance: A South African case study - Christiaan Hattingh; André de Waal; Phillip Parsons (South African Journal of Business Management, 2018)
The dual challenge of globalisation of competition and global economic slowdown has increasingly forced businesses to do introspection not only in terms of their cost structures, but also in terms of their value proposition in search of sustainable organisational success. Given the limited influence that organisations, in general, have over their external environments, organisations have become more focussed on identifying internal constraints that inhibit rapid responses to market challenges and opportunities, and on identifying the interventions that are most critical to address these Issues. This study focussed on the organisational characteristics that drive high performance, derived from De Waal's high-performance organisation (HPO) framework, and proposed interventions to enhance the development of a high performance culture within the case company. Employing a self-administered questionnaire, it was possible to determine the performance of the case company across a range of five critical dimensions for high performance. A detailed analysis of each of the 35 questions provided an in-depth picture of the organisation's strong and weak points and, from this analysis, specific actions to address the areas of weakness were identified. The study confirmed the robustness of the HPO framework employed as well as demonstrating its usefulness to management in terms of a detailed analysis of where the organisation was positioned in terms of the various high performance factors that are linked to organisational success.
Keywords: 650